Transnational governance standards in ensuring sustainable development and operation of hydropower projects in transboundary basins - McIntyre, Owen (Frontiers in Climate, 2024)
The notion of “transnational” law encompasses a sophisticated corpus of globally applicable rules, standards and safeguards, often informal in origin, which are widely accepted around the world and supported across a range of business sectors and civil society constituencies. The recent proliferation of such “transnational” law extends to the hydropower sector, where normative standards and safeguards increasingly apply to promote and certify sustainable practices in the development and operation of hydropower projects. Such projects are associated with significant environmental and social impacts and the projected increase in hydropower investments, mainly in emerging economies, will require effective supplemental regulatory tools. Many such projects will be located in, or impact upon, international rivers, thereby adding a further layer of complexity regarding their effective regulation and increased the risk of inter-State disputes over the equitable use of shared waters. Such complexity and risk will be exacerbated by increased uncertainty due to climate change. Thus, the existence of widely accepted transnational standards, which are relevant and applicable to hydropower development globally, can play a key role in building trust between watercourse States and in promoting greater transboundary water cooperation. This article explores the potential role of transnational standards in improved regulation of environmental and social impacts associated with hydropower projects located on international watercourses and the extent to which such standards cohere with established and emerging requirements of international water law. It thus examines the synergies arising between these informal and formal regulatory frameworks with a view to developing a better understanding of their interaction in practice. In so doing, it focuses on two key categories of applicable transnational regime: a sustainability certification and labeling scheme dedicated to hydropower projects and operated by the Hydropower Sustainability Council; and MDB environmental and social safeguard standards imposed upon major water-related projects, including hydropower projects, particularly those adopted by the World Bank and the European Bank for Reconstruction and Development (EBRD).